NEW APPROACHES IN ELECTROPHORESIS - Gunestutar, Leman Yalcintepe; Rodop, Macide Canturk (YILDIZ TECHNICAL UNIV, 2009)
Electrophoresis is a technique used to separate and sometimes purify macromolecules - especially proteins and nucleic acids - that differ in charge, size or shape. It is one of the most widely-used techniques in biochemistry and molecular biology.
Keywords: Mobility; electric field; electrophoresis; proteomics; cancer; Engineering